Legal Protection for Consumers of Life Insurance: A Review of Consumer Protection Laws - Vanya Lakhsitta Az Zahra; Wida Daning Mulia; Luthfia Nurhaliza Wirawan; Najla Adizahra (Proceeding International Conference Restructuring and Transforming Law, 2024)
This article investigates the legal protection afforded to consumers within the context of life insurance, focusing on the Consumer Protection Act. The review aims to analyze the mechanisms of protection available to life insurance consumers and identify the challenges and opportunities encountered in implementing this legislation. This study employs a descriptive-analytical approach by examining various legal provisions related to consumer rights and obligations, as well as the responsibilities of life insurance providers. The findings provide insights into the effectiveness of consumer protection regulations in safeguarding consumer interests in life insurance transactions and identify areas where further improvements are needed within the consumer legal protection system. This research may serve as a valuable resource for legal practitioners, regulators, and other life insurance stakeholders in strengthening consumer protection and enhancing fairness in consumer-provider relationships.